If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2v+3)+8=6(v-1)+3v
We move all terms to the left:
2(2v+3)+8-(6(v-1)+3v)=0
We multiply parentheses
4v-(6(v-1)+3v)+6+8=0
We calculate terms in parentheses: -(6(v-1)+3v), so:We add all the numbers together, and all the variables
6(v-1)+3v
We add all the numbers together, and all the variables
3v+6(v-1)
We multiply parentheses
3v+6v-6
We add all the numbers together, and all the variables
9v-6
Back to the equation:
-(9v-6)
4v-(9v-6)+14=0
We get rid of parentheses
4v-9v+6+14=0
We add all the numbers together, and all the variables
-5v+20=0
We move all terms containing v to the left, all other terms to the right
-5v=-20
v=-20/-5
v=+4
| 1.6x-4.5x=39-2.3x | | 5(x-1)+3(2x+9)-2=4(3x-1)+2(4x+3) | | 7(5v-3)-6(5v-3)=42 | | 0=1.7x-3.9 | | -6+7x=7x-6 | | 86=2w+2(3w) | | 4(3y+8)=y+3=128 | | 68=−(11−2s)−(7s+1) | | −(11−2s)−(7s+1)=68 | | 10+7w=7+13w | | 0,2x+150=0,4x+80 | | d+2d-5=4 | | (x+8)^(-5)=64 | | 3(5u+5)=174-2(5u-8) | | 165x+1=26 | | 1/4*(x-2)+4=12 | | 2x2-9x-18=0 | | -2*(7-y)+4=-4 | | 5x+27=68 | | 7x/3−44=12−5x/3 | | 2y-29=29 | | 2/3w-1/2=-7/2w-3 | | -3/2v-7/5=6v+3/5 | | y=-225+13200 | | 6+-2(x+6)=3x+4 | | 5x6,67+30=2x+50 | | 5x+30=2x+50 | | 32/3•n=2/9 | | 5/8•n=55 | | -3y-10=(4y+8)+2y | | {4y+3}{7}=9 | | F(4)=1/(x+5)^2 |